No, to see that this is not true, you could just plug in 0. However it is true that 1+ (tanx)^2 = (secx)^2.
Fortunately, you do not have to remember this -- I sure as heck can't. You just have to remember that:
(sinx)^2 + (cosx)^2 = 1
Then to get a relation with tanx and secx, just divide all the terms by (cosx)^2 to get:
(tanx)^2 + 1 = (secx)^2
You can also divide (sinx)^2 + (cosx)^2 = 1 through by (sinx)^2 to get:
1 + (cotx)^2 = (cscx)^2
2007-01-30 15:29:39
·
answer #1
·
answered by Phineas Bogg 6
·
0⤊
0⤋
No - that's backwards. We know sin^2 x + cos^2 x = 1. Divide through by cos^2 x, and we get tan^2 x + 1 = sec^2 x, which is the correct identity. tan^2 x = sec^2 x - 1.
2007-01-30 15:32:07
·
answer #2
·
answered by airtime 3
·
0⤊
1⤋
1 + sec(x)^2 = 1 + (1/cos(x))^2 = (1 + cos(x)^2)/(cos(x)^2))
tan(x)^2 = (sin(x)/cos(x))^2 = (1 - cos(x)^2)/(cos(x)^2)
so for 1 + sec(x)^2 to equal tan(x)^2, you have to have 1 - sec(x)^2
2007-01-30 15:48:14
·
answer #3
·
answered by Sherman81 6
·
1⤊
0⤋
yes
2007-01-30 15:29:47
·
answer #4
·
answered by Anonymous
·
0⤊
3⤋
yes
2007-01-30 15:28:45
·
answer #5
·
answered by Lala Girl 2
·
0⤊
3⤋
no
2007-01-30 15:32:50
·
answer #6
·
answered by m m 3
·
1⤊
0⤋
www.calculator.com
2007-01-30 15:29:53
·
answer #7
·
answered by vlad|KARNAFËL 【KOR】 3
·
0⤊
1⤋
Indeed it is.
2007-01-30 15:28:50
·
answer #8
·
answered by Steady As She Goes 2
·
0⤊
3⤋